Seven women portraits from the American radical tradition - Nies, Judith 1941- (Viking Press, 1977)
Brief biographies of seven women whose philosophies and actions have had great impact on American society: Sarah Moore Grimke, Harriet Tubman, Elizabeth Cady Stanton, Mother Jones, Anna Louise Strong, Charlotte Perkins Gilman, and Dorothy Day.